Selecting Nanobodies Specific for the Epidermal Growth Factor from a Synthetic Nanobody Library - Yunier Serrano-Rivero; Julieta Salazar-Uribe; Marcela Rubio-Carrasquilla; Frank Camacho-Casanova; Oliberto Sánchez-Ramos; Alaín González-Pose; Ernesto Moreno (Molecules, 2023)
The epidermal growth factor (EGF) is one of the most critical ligands of the EGF receptor (EGFR), a well-known oncogene frequently overexpressed in cancerous cells and an important therapeutic target in cancer. The EGF is the target of a therapeutic vaccine aimed at inducing an anti-EGF antibody response to sequester this molecule from serum. However, strikingly, very few investigations have focused on EGF immunotargeting. Since the use of nanobodies (Nbs) for EGF neutralization may be an effective therapeutic strategy in several types of cancer, in this study, we decided to generate anti-EGF Nbs from a recently constructed, phage-displaying synthetic nanobody library. To our knowledge, this is the first attempt to obtain anti-EGF Nbs from a synthetic library. By applying a selection strategy that uses four different sequential elution steps along with three rounds of selection, we obtained four different EGF-specific Nb clones, and also tested their binding capabilities as recombinant proteins. The obtained results are very encouraging and demonstrate the feasibility of selecting nanobodies against small antigens, such as the EGF, from synthetic libraries.